Sea‐surface temperature anomalies mediate changes in fish richness and abundance in Atlantic and Gulf of Mexico estuaries. (12th July 2022) - Oke, Tobi A.; Zhang, Stacy Y.; Keyser, Spencer R.; Yeager, Lauren A.
Abstract: Aim: Anthropogenic warming of marine systems has caused biological and physiological responses that are fundamentally altering ecosystem structure. Because estuaries exist at the land‐ocean interface, they are particularly vulnerable to the effects of ocean warming as they can undergo rapid biogeochemical and hydrological shifts due to climate and land‐use change. We explored how multiple components of estuarine fish diversity—turnover, richness, and abundance—have changed in the North Atlantic and Gulf of Mexico estuaries across space and time and the drivers of change. Location: North Atlantic and Gulf of Mexico. Taxa: Fish. Method: We compiled long‐term (>30 years), continent‐wide fisheries independent trawl surveys conducted in estuaries—from the Gulf of Maine to the Gulf of Mexico (U.S. waters)—and combined these with climate and land‐use‐land‐cover data to examine trends and ecological drivers of fish richness, abundance and turnover using mixed‐effect models. Results: Species richness, abundance and turnover have increased in North Atlantic and Gulf of Mexico estuaries in the last 30 years. These changes were mediated largely by sea‐surface temperature anomalies, especially in more northern estuaries where warming has been relatively pronounced. Main Conclusion: The increasing trajectory of turnover in many estuaries suggests that fish communities have changed fundamentally from the baselines. A fundamental change in community composition can lead to an irreversible trophic imbalance or alternative stable states among other outcomes. Thus, predicting how shifting community structures might influence food webs, ecosystem stability, and human resource use remain a pertinent task.